Finnegan Connection : Shadows in the Night -Book 2 - Graham, Heather ([New York] : Harlequin Enterprises, 2017)
Listeners can enjoy two stories by Heather Graham that include Shadows in the Night; and Never Sleep With Strangers.
Keywords: United States. -- Federal Bureau of Investigation -- Officials and employees; Fiction; Man-woman relationships; Fiction; Murder -- Investigation; Fiction; Romance fiction; Audiobooks